Promising reciprocity: When proposing a favor for a request increases compliance even if the favor is not accepted. Issue 5 (2nd September 2016) - Guéguen, Nicolas; Meineri, Sébastien; Ruiz, Clément; Pascual, Alexandre
ABSTRACT: Research has reported that reciprocity is an important social norm in relationships. In previous studies on reciprocity, participants' behavior was examined after receiving a favor from someone. In a series of field studies, we examined the effect of a statement that proved that a solicitor was someone who respected this principle. Confederates solicited participants for money or a cigarette in exchange for stamps or money, respectively. It was found that the participants complied more readily with the request in the promised favor condition, but most of them refused to take the promised favor. We conclude that individuals were led to help those who respected the putative norm of reciprocity in their social interaction.